User Perception of Quality in Sports Websites (Laisvalaikio tyrimai, 2023)
Relevance of the topic. The 21st century is widely regarded as the age of technology. Nowadays, no one can imagine their life without browsing various websites. As Gonzalez et al. (2015) state, websites are a dominant place for users to obtain information. Many professional sports organisations use their websites to develop relationships with their fans by providing them with news and results (Alonso-Dos-Santos, Moreno, Ríos, & Alguacil, 2017). Sports websites are especially useful for sports enthusiasts, as sports is a very globalised activity and it is physically impossible to be at all desired events. Fans are not only more engaged and interested in their favourite teams but also in their websites, thus performing a kind of news distribution function for the club (Lewis, 2013). The problem. The widespread use of information technology in various felds has made research on the adoption or rejection of these technologies an important factor in every organisation (Mohammadi & Isanejad, 2018). The rapid change and development of websites mean that users’ perception of their quality is also changing. Therefore, it is important to track the constantly changing user expectations and their engagement. A newer and more up-to-date study can help organisations to further improve their websites, thus competing with other organisations in their market.The aim of the study is to investigate user perception of quality in sports websites.The subject of the study is user perception of quality in sports websites. Research methodology. A survey was used to investigate user perception of quality in sports websites. Respondents were given an anonymous online survey. The object of the study was user perception of quality in sports websites. The study was based on the WebQual questionnaire of Gonzalez et al. (2015). The purpose of the study is to investigate user perception of quality in sports websites. The data were collected in February and March 2023. A total of 303 respondents participated in the study. Results and conclusion. A comparison of the distribution of respondents according to which website they would prefer shows that all analysed categories reﬂect a trend. In all four question categories, the better-rated website was X website and when respondents were asked to choose between these websites, the vast majority (69.31%) would prefer X website, while 30.69% of respondents would choose Y website. This result means that among these competing basketball websites, X website seems to be more attractive and high-quality for most users. The results of the study allowed to understand what quality criteria aﬀect the opinion and choice of sports websites by users. Comparing the results obtained with other previous studies, it was observed that individual categories or subcategories can not only inﬂuence the choice of a website but can also interact with each other, thus aﬀecting each other. An analysis of the survey results showed that the accuracy of information, security, website understandability, security and website attractiveness are the main features that positively aﬀect the user and help websites gain a competitive advantage over other websites in the same feld or market.Keywords: sports website, user perception of quality, engagement.